Medicinal plant use practice in four ethnic communities (Gurage, Mareqo, Qebena, and Silti), south central Ethiopia - Teka, Alemtshay; Asfaw, Zemede; Demissew, Sebsebe; Van Damme, Patrick (Journal of ethnobiology and ethnomedicine, 2020)
BACKGROUND: Ethnic groups throughout the world have developed their own cultures expressed in the form of customs, taboos, and traditional healthcare systems. Traditional medicine system is one of the widespread cultures known throughout the world which is very much tied to cultural practices of the community or ethnic group. Medicinal plant treasure found in Gurage and Silti zones remained poorly characterized and understood. Therefore, this study was conducted in four ethnic groups: three from Gurage zone (Gurage, Qebena, and Mareqo) and one from Silti zone (Silti) which have lived in close proximity and contact for many centuries in the respective zones. In the present study, unique and shared cultural elements in connection to traditional herbal medicine were examined through investigation of the diversity of medicinal plants. Moreover, attempts have been made to determine similarities among the society in the medicinal plants they have used in general and in medicinal plant species considered culturally most important. METHODS: In a study that involved 320 randomly sampled informants, semi-structured interviews, focus group discussions, and participant observation were used and qualitative and quantitative data were collected. Descriptive statistics, rank order priority (ROP), informant consensus factor, Jaccard similarity coefficient, and clustering were used for data analysis. RESULTS: A total of 244 medicinal plant species and a fungal species used to treat human and/or livestock ailments were documented. The number of plants (80 plants, 33 %) with ROP value greater than 50% were considerably fewer than that of plants with ROP < 50% (164, 67 %). Jaccard similarity index and clustering analysis for all cited plants, among the respective studied districts, indicated that grouping generally followed the existing ethnic origin. On the contrary, clustering based on culturally important medicinal plant species (80 plant species, score ROP ≥ 50%) showed the influence of proximity and geographical orientation rather than ethnic relation. CONCLUSIONS: Culturally, most important plants (80 spp.) are widely used and best shared with nearby communities and this could imply current (new) knowledge being practiced in the communities. This knowledge must be documented and better utilized in a modern way including modernized use of traditional medicinal plants.
Keywords: etnofarmakologie; léčivé rostliny; Mareqo; Qebena; Ethnicity; Ethnopharmacology; Ethnic groups; Gurage; Medicine, African Traditional; Plants, Medicinal; znalosti; Silti; Traditional knowledge; Culture; Humans; Etiopie; Knowledge; etnicita; Ethiopia; tradiční africká medicína; lidé; Medicinal plants